EFEKTIVITAS MODEL PEMBELAJARAN GROUP INVESTIGATION TERHADAP HASIL BELAJAR MATEMATIKA KELAS 5 SEKOLAH DASAR - Nur Syifa’ul Alyah; Bilal Abdul Aziz; Imam Saputra (Universitas Islam Nahdlatul Ulama Jepara, 2020)
This research is motivated by the fact that the mathematics learning process is less than optimal, seen from the incomplete learning outcomes of the students. The purpose of this study was to determine the effectiveness of using the group investigation learning model in improving mathematics student learning outcomes in the material. The approach used in this research is a quantitative approach with the experimental method nonequivalent control group design. Sampling using nonprobability sampling. The data collection technique was obtained from a multiple choice written test. The data analysis technique used descriptive and statistical analysis with the help of the SPSS version 21 application. The results showed that data processing using the independent sample test data posttest experimental class and control, showed the sig value. (2-tailed) of 0.042, which means that it is smaller than 0.05. According to the basis of decision making in the independent sample t test, if the sig. (2-tailed) value <0.05 then Ha is accepted and H0 is rejected, or in other words there is a significant difference between the experimental and control classes in improving student learning outcomes in the material Build a 5th grade Mathematics subject room. Thus, the group investigation learning model was effective in improving mathematics learning outcomes for grade 5 SD at SDIT Ali Bin Abi Thalib, Sendang Village, Kalinyamatan District. Keywords: Learning Outcomes, Learning Models, Group Investigation